2011
DOI: 10.1097/mat.0b013e3182377216
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis Patients' Fluid Overload, Antihypertensive Medications, and Obesity

Abstract: Overhydration (OH) is both a major etiology of hypertension in hemodialysis patients and a serious risk factor for mortality. We investigated the association of multiple variables and OH. This is a cross-sectional study of prevalent hemodialysis patients examining the predialysis hydrational status with a portable bioimpedance apparatus to measure the degree of hydration. We completed our study in 79 patients. Patients were overhydrated by 2.6 ± 2.4 L. The mean medication count was 2.4 ± 1.5, and 50.7% had diu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
26
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
5
26
0
2
Order By: Relevance
“…A recent study in 79 dialysis patients aiming at a reduction of blood pressure and antihypertensive medication, yielded interesting results with regard to a lower percentage of body fat in fluid overloaded dialysis patients [37]. These findings are in accordance with our results enforcing the view that underweight patients are more susceptible to fluid overload, whereas adipose patients tend to be in an underhydrated condition.…”
Section: Discussionsupporting
confidence: 91%
“…A recent study in 79 dialysis patients aiming at a reduction of blood pressure and antihypertensive medication, yielded interesting results with regard to a lower percentage of body fat in fluid overloaded dialysis patients [37]. These findings are in accordance with our results enforcing the view that underweight patients are more susceptible to fluid overload, whereas adipose patients tend to be in an underhydrated condition.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies using bioimpedance analysis showed that overhydration is prevalent in leaner patients undergoing dialysis therapy [3,20]. Overhydration might be less apparent in obese patients [21,22]. Malnutrition-inflammation complex syndrome in those patients may partly explain the existence of the ‘obesity paradox'.…”
Section: Discussionmentioning
confidence: 99%
“…Tal fato pode repercutir na baixa adesão ao regime terapêutico, visto que a escolaridade deficiente pode dificultar a compreensão acerca do processo de saúde-doença, além do entendimento do tratamento a ser instituído, o qual requer intervenções específi-cas, complexas, e cuja obediência é fundamental à sua eficácia. Outrossim, o cumprimento do regime terapêutico é crucial na determinação da sobrevida desses pacientes, tendo em vista as complicações tanto da sobrecarga hídrica, como as repercussões negativas da retirada excessiva de líquidos (10)(11)14).…”
Section: Discussionunclassified
“…Desse modo, em pacientes com maior IMC foi detectada a menor ocorrência da sobrecarga de volume de líquidos. Em contrapartida, um índice de massa corporal inferior é conhecido por ser fortemente associado com o aumento da mortalidade na população em hemodiálise e particularmente naqueles com sobrecarga do volume de líquidos (11,14,19).…”
Section: Discussionunclassified